Antioxidants intake and status, and oxidative stress in relation to breast cancer risks : a case-control study. - Shahar, Suzana; H., Normah; Abu Bakar, Fatimah; Rajab, Nor Fadilah; Ghazali, Ahmad Rohi; Ismail, Amin; Cham, B. G.; R., Mohd Rizal; Md. Noh, Mohd Fairulnizal (Asian Pacific Education Press Ltd., 2008)
A case control study was carried out to investigate associations between breast cancer risk, antioxidant status and oxidative stress among women in Klang Valley and Selangor. A total of 57 newly diagnosed cases aged 30 to 66 years old participated and were matched for age and ethnicity with 139 controls with no diagnosis of cancer or other chronic diseases. An interview based questionnaire designed to collect information on demographic and socioeconomic status, as well as reproductive, medical and dietary history was used. Anthropometric measurements including weight, height, waist and hip circumference were made and a 10 ml fasting venous blood sample was taken for glucose testing and analysis of plasma vitamin antioxidants and malondialdehyde. Hair and toenail samples were taken for selenium analysis. Results showed that the mean intake of vitamin A, vitamin E and selenium among cases (606.8±334.8μg/d, 6.1± 2.4 g/d, 56.9 ± 16.2 μg/d) was lower than controls (724.7 ± 414 μg/day, 6.9 ± 3.0 g/d, 60.8 ± 17.5 μg/d, respectively) (p<0.05 for all parameters). A similar trend was noted for plasma vitamin A and E and also selenium in hair and toenails. Poor antioxidant status as indicated by low plasma vitamin A (<284.3 μg/l or <366.3 μg/l) increased risk of breast cancer by approximately two fold, whilst low plasma vitamin E (<2.5 mg/dl, <2.8 mg/dl and <3.1 mg/dl) increased the risk by two to three fold [Adjusted OR 2.97 (95% CI 1.38-3.48), 2.32 (95% CI 1.07-2.41) and 2.12 (95% CI 1.00-4.21)]. Cases had a greater level of malondialdehyde 4.4 ± 1.1 mmol/g protein), an indicator of oxidative stress, as compared to controls (3.2 ± 1.7 mmol/g protein)(p<0.05). A high level of MDA (≥4.8 mmol/g protein) was associated with breast cancer [Adjusted OR 6.82 (95% CI 1.95-23.9)]. It is concluded that a poor antioxidant status and high oxidative stress are associated with breast cancer risk. Thus, it is essential for Malaysian women to obtain a good antioxidant status by consuming a diet rich in vitamins A and E as well as selenium and adopt healthy behaviour to reduce oxidative stress in order to prevent breast cancer.